Modern Theoretical Aspects of the Institute of International Protection and Promotion of the Rights of the Child - Katazhina Nikonov (Московский журнал международного права)
International protection and promotion of the rights of the child has been evolving from the ancient times. However, the modern phase of its development began in 1945 with the establishment of the Organization of the United Nations. In this article the author shows how the evolution of the international protection of the human rights, especially of the rights of the child, resulted in development of the separate institute of the international protection and promotion of human rights regarded as separate branch of the international law. In the article you will find the argumentation of the emphasis made on the special protection of the rights of the child, as well as their promotion presented. The author adduces arguments with regard to the common rules and principles of the system of law theory itself, evaluation of the conceptual categories: “human being” and “child”, as well as evaluation of the equality of the rights of all humans with respect to special protection of the rights of the child and some limitations of the rights of infants and minors. In the last part of the article the author provides the separate classification of the sources of the institute of international protection and promotion of the rights of the child.